Organizational commitment of health professionals and associated factors in primary healthcare facilities of Addis Ababa, Ethiopia: A multi-center cross-sectional study - Arage, Sulyeman Mohammed; Daba, Derese Bekele; Dessalegn, Abere Yekoye (Frontiers in Public Health, 2022)
BACKGROUND: Organizational commitment has a positive impact on an organization's ability to provide professional services. Committed human power pushes an organization to achieve its goals. But non-commitment can lead increased occurrence of medical errors, increases in the longevity of inpatient day admissions, and redundancy of hospitalizations leading to low quality of health care. However, to the best of the knowledge of researchers, there are no studies examining organizational commitment in the health care setting of Addis Ababa, Ethiopia. OBJECTIVE: To assess the level of organizational commitment and associated factors among health professionals working in the primary health facility of Addis Ababa, Ethiopia. METHODS: A facility-based cross-sectional study was conducted among 459 health care professionals selected by simple random sampling from 12 health centres. Data were collected by three data collectors and one supervisor using a pretested questionnaire. Data were checked for completeness, cleaned, and entered into Epi-Data version 3.1.and exported into SPSS version 25 for analysis. In binary logistic regression statistical analysis, variables (p<0.25) were entered in multiple binary logistic regression analyses. Then the regression result was presented using COR, AOR with 95% CI and a p-value less than 0.05 as a level of significance RESULT: The respondent’s percent mean score of organizational commitment was 48.4%. Age group above 30 years (AOR=1.52, 95% CI, 1.01, 2.30), those who were satisfied with their job (AOR 2.02, 95% CI 1.30, 3.13) and those who perceive good transformational leadership behaviour [AOR: 1.85, 95% C.I, 1.18, 2.90] were significant factors of organizational commitment among health professionals. CONCLUSION AND RECOMMENDATION: Organizational commitment was lower in magnitude in the study setting. Age, job satisfaction, and transformational leadership behaviour were significant predictors of organizational commitment